Role of sports in national policies in opinions of Russian politicians and citizens - Grishanina, A. N.; Melnik, G. S.; Sveshnikova, N. O.; Olesich, N. Y. (Theory and Practice of Physical Culture, 2018)
The study analyzes results of the questionnaire survey of the Russian population to poll the public attitudes to the Olympics in Vancouver where the Russian team ended up unusually low on the scoreboard. The questionnaire survey was designed to obtain opinions of ordinary residents, politicians and government officers on the role of sports in the national policies. The study data and analysis confirmed the hypothesis of a certain correlation between the sport conceptions formed by the government offices and public attitudes to sports. The study applied the Schwartz test to find the respondents` values and priorities in the sports domain. The government officers` opinions were rated by the content analysis of their speeches on sport matters. Correlation analysis of the survey data showed that the respondents tend to accept sports as a genuine component of healthy lifestyle, good business for young people, professional field, and a critical part of the national culture. It is important that the respondents generally accept modern sports as a part of governmental policies albeit their attitudes to the latter are expressly negative on the whole.